Urgensi Kerahasiaan Data Anak dalam Proses Peradilan Pidana Untuk Kepentingan Terbaik Bagi Anak - Hanafi Pasaribu, Yusuf (DOKTRINA: JOURNAL OF LAW, 2026)
This research discusses the confidentiality of children's data as a manifestation of the best interests of the child, the legal basis for the confidentiality of children's data in criminal justice, and the impacts of identity disclosure and data breaches involving children in criminal cases, including stigma, revictimization, and digital footprints. The results showed that revealing a child's identity can lead to stigma, bullying, cyberbullying, and revictimization, and leave a digital footprint that is difficult to recover. This condition has the potential to thwart the goals of juvenile justice, namely recovery, coaching, and social reintegration. Normatively, law of the Republic of Indonesia No. 11 of 2012 concerning the juvenile criminal justice system requires the confidentiality of the identity of children, victims and witnesses, regulates hearings in closed hearings, and contains sanctions for violations. This protection is also in accordance with the law of the Republic of Indonesia number 23 of 2002 on child protection as amended and Law of the Republic of Indonesia number 27 of 2022 on Personal Data Protection. The study recommends anonymizing rulings, restricting file access, reporting guidelines, and quick steps to remove or limit the distribution of content that contains a child's identity.